Generating political commitment for ending malnutrition in all its forms: A system dynamics approach for strengthening nutrition actor networks. (27th June 2019) - Baker, Phillip; Brown, Andrew D.; Wingrove, Kate; Allender, Steve; Walls, Helen; Cullerton, Katherine; Lee, Amanda; Demaio, Alessandro; Lawrence, Mark
Summary: Generating political commitment for ending all forms of malnutrition represents a key challenge for the global nutrition community. Without commitment, the policies, programs, and resources needed to improve nutrition are unlikely to be adopted, effectively implemented, nor sustained. One essential driver of commitment is nutrition actor network (NAN) effectiveness, the web of individuals and organizations operating within a given country who share a common interest in improving nutrition and who act collectively to do so. To inform new thinking and action towards strengthening NAN effectiveness, we use a systems dynamics theoretical approach and literature review to build initial causal loop diagrams (CLDs) of political commitment and NAN effectiveness and a qualitative group model building (GMB) method involving an expert workshop to strengthen model validity. First, a "nutrition commitment system" CLD demonstrates how five interrelated forms of commitment—rhetorical, institutional, operational, embedded, and system‐wide—can dynamically reinforce or diminish one another over time. Second, we present CLDs demonstrating factors shaping NAN effectiveness organized into three categories: actor features, resources, and capacities; framing strategies, evidence, and norms; and institutional, political, and societal contexts. Together, these models generate hypotheses on how political commitment and NAN effectiveness could be strengthened in future and may provide potential starting points for country‐specific conversations for doing so.